Integrated self-supporting gas phase diffusion electrode, preparation method and application

Through an integrated self-supported gas-phase diffusion electrode preparation method, the problems of low utilization rate and poor stability of traditional electrodes during electrocatalysis are solved, and efficient and stable electrocatalytic reaction is achieved.

CN119640299APending Publication Date: 2025-03-18SHENZHEN INST OF ADVANCED TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411726665.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

During the electrocatalysis process, traditional gas-phase diffusion electrodes have problems such as low utilization rate of the total active center of the catalyst, serious hydrogen evolution at high current density, and poor stability during electrolysis.

Method used

A method of preparing an integrated self-supported gas-phase diffusion electrode is adopted. By mixing conductive materials, catalysts and pore-forming agents to form mixed powders, mixed with hydrophobic polymers, ball milling, and finally heat treatment is carried out to avoid the use of binders, ensuring that the catalyst is limited inside the gas-phase diffusion layer, thereby improving the utilization rate of the active center and enhancing the stability of the electrode.

Benefits of technology

The total active center utilization rate of the catalyst is significantly improved, effectively preventing the catalyst from falling off, enhancing the selectivity of electrocatalytic reactions under high current density, and improving the operating stability of the entire electrolytic system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640299A_ABST
    Figure CN119640299A_ABST
Patent Text Reader

Abstract

According to the integrated self-supporting gas phase diffusion electrode, the preparation method and the application, the conductive material, the catalyst and the pore forming agent are mixed to form the mixed powder, the mixed powder, the organic solvent and the hydrophobic high-molecular polymer are mixed and subjected to ball milling to obtain the electrode blank, the electrode blank is subjected to heat treatment, and the integrated self-supporting gas phase diffusion electrode is obtained. In the preparation process, a binder does not need to be used, the catalyst is limited in the gas phase diffusion layer in the preparation process, the total active center utilization rate of the catalyst is increased, and meanwhile the catalyst can be effectively prevented from falling off in the electrolysis process; besides, compared with a planar two-dimensional three-phase interface, a stable hydrophobic microenvironment and an efficient electron transmission channel are constructed around the catalyst, contact sites of the three-phase interface are remarkably increased, and the operation stability of the whole electrolysis system is enhanced while the electro-catalytic reaction selectivity under high current density is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrocatalysis technology, and in particular to an integrated self-supporting gas-phase diffusion electrode, a preparation method and an application thereof. Background Art

[0002] Many researchers believe that the three-phase interface of the gas diffusion electrode is the key area for the actual electrocatalytic reaction. The electrocatalytic performance depends to a large extent on the design optimization of the gas diffusion electrode. The most ideal integrated self-supporting gas diffusion electrode must ensure that the gas reactants and liquid electrolytes coexist inside the electrode and can effectively interact with each other on the catalyst surface.

[0003] The three-phase interface is not only the intersection of gas, liquid and solid phases, but also the key place for the interaction between reactant molecules, protons and electrons. Taking electrocatalytic CO2 reduction as an example, in the complex interface of gas phase diffusion electrode, CO2 molecules need to interact with H on the catalyst surface. + At the same time, electrons must quickly transfer from the electrode to the catalyst surface. During the entire reaction process, these factors are coupled to each other and jointly affect the behavior of gases, protons and electrons as well as the activity and selectivity of electrocatalysis.

[0004] The traditional gas diffusion electrode is composed of a carbon fiber substrate (CFS), a microporous layer (MPL) and a catalytic layer (CL), and CFS and MPL constitute the gas diffusion layer.

[0005] In the layered structure, the combination of the catalyst layer and the gas diffusion layer often relies on ionic polymer binders such as Nafion. However, the performance of this combination strategy in the electrolysis process is not ideal. First, the binder will fill the pores of the gas diffusion electrode and hinder the effective diffusion of gas molecules; second, the use of the binder will cause the active sites to be blocked, interfere with the electron transmission process, and make the total active center utilization of the catalyst low; finally, the degradation of the binder will cause the catalyst particles to gradually peel off from the electrode surface, thereby affecting the catalytic efficiency of the electrode and the sustainability of the overall performance.

[0006] Although MPL is composed of carbon powder and polytetrafluoroethylene (PTFE) particles, which can keep the liquid and gas phases separated, the catalyst particles on the surface of the gas diffusion electrode will still be wetted by the electrolyte due to the lack of hydrophobicity. Especially under high current density, the interface between MPL and CL suffers rapid erosion, causing water flooding and severe hydrogen evolution. These factors jointly limit the mass transfer and charge transfer dynamics of the electrocatalytic reaction, posing a severe challenge to the selectivity and stability of the electrocatalytic reaction. Summary of the invention

[0007] In view of this, it is necessary to provide a preparation method, an integrated self-supporting gas-phase diffusion electrode and its application with high current density, high efficiency and stability to address the defects of current gas-phase diffusion electrodes in the electrocatalytic process, such as low utilization of the total active centers of the catalyst, severe hydrogen evolution at high current density and poor stability during electrolysis.

[0008] To solve the above problems, this application adopts the following technical solutions:

[0009] One of the purposes of the present application is to provide a method for preparing an integrated self-supporting gas diffusion electrode, comprising the following steps:

[0010] Mixing a conductive material, a catalyst and a pore-forming agent to form a mixed powder;

[0011] Mixing the mixed powder, organic solvent and hydrophobic high molecular polymer and ball milling to obtain an electrode blank;

[0012] The electrode blank is heat treated to obtain the integrated self-supporting gas phase diffusion electrode.

[0013] In some embodiments, the mass ratio of the catalyst to the conductive material is 1:50-50:1; the mass of the pore former is 0-50% of the total mass of the mixed powder; and the mass ratio of the hydrophobic polymer to the conductive material is 1:1-50:1.

[0014] In some embodiments, the conductive material is in powder form, and the conductive material includes but is not limited to at least one of graphite, graphene, carbon nanotubes, acetylene black, Ketjen black, conductive carbon black, and activated carbon.

[0015] In some embodiments, the catalyst is in powder form, and the catalyst includes but is not limited to at least one of silver powder, copper powder, bismuth powder, nickel powder, cobalt powder, cupric oxide, cuprous oxide, bismuth oxide, copper-silver alloy, copper-tin alloy, copper-zinc alloy, copper-nickel alloy, and nitrogen-doped carbon powder.

[0016] In some embodiments, the pore-forming agent is in powder form, and the pore-forming agent includes but is not limited to at least one of polyethylene glycol, polyvinyl alcohol, polyvinyl chloride, polymethyl methacrylate, and polylactic acid.

[0017] In some embodiments, the organic solvent includes but is not limited to at least one of ethanol, isopropanol, methanol, ethyl acetate, acetonitrile, N-methylpyrrolidone, and dimethylformamide.

[0018] In some of the embodiments, the hydrophobic polymer includes but is not limited to at least one of polytetrafluoroethylene, expanded polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polystyrene, and polypropylene.

[0019] In some of the embodiments, in the step of ball-milling the mixed powder, organic solvent and hydrophobic high molecular polymer to obtain an electrode blank, the ball-milling speed is 100-2000 rpm and the ball-milling time is 10-720 min.

[0020] In some of the embodiments, after the step of mixing and ball-milling the mixed powder, organic solvent and hydrophobic polymer to obtain an electrode blank, the following step is also included: rolling and shaping the electrode blank to obtain a sheet electrode, the rolling interval is 0.01-5mm, and the thickness of the sheet electrode is 50-500μm.

[0021] In some embodiments, the step of heat treating the electrode blank to obtain the integrated self-supporting gas diffusion electrode specifically includes the following steps:

[0022] The electrode blank is heated to 100-400° C. at a heating rate of 1-20° C. / min and kept at this temperature for 0.5-5 h.

[0023] The second object of the present application is to provide an integrated self-supporting gas diffusion electrode, which is prepared by any of the methods for preparing an integrated self-supporting gas diffusion electrode described above.

[0024] The third purpose of the present application is to provide an application of the integrated self-supporting gas diffusion electrode in an electrocatalytic reaction.

[0025] This application adopts the above technical solution, and its beneficial effects are as follows:

[0026] The integrated self-supporting gas diffusion electrode, preparation method and application provided by the present application are as follows: a conductive material, a catalyst and a pore-forming agent are mixed to form a mixed powder, the mixed powder, an organic solvent and a hydrophobic high molecular polymer are mixed and ball-milled to obtain an electrode blank, and the electrode blank is heat-treated to obtain the integrated self-supporting gas diffusion electrode. In the above preparation process, no binder is required, but the catalyst is confined to the inside of the gas diffusion layer during the preparation process, which can effectively prevent the catalyst from falling off during the electrolysis process while improving the utilization rate of the total active center of the catalyst; in addition, compared with the planar two-dimensional three-phase interface, the present application constructs a stable hydrophobic microenvironment and an efficient electron transmission channel around the catalyst, which significantly increases the contact sites of the three-phase interface, while improving the selectivity of the electrocatalytic reaction under high current density and enhancing the operating stability of the entire electrolysis system. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0028] Figure 1 A flow chart of the steps of the method for preparing an integrated self-supporting gas diffusion electrode provided in an embodiment of the present application.

[0029] Figure 2 This is a SEM schematic diagram of the integrated self-supporting gas diffusion electrode provided in Example 5 of the present application.

[0030] Figure 3 This is a bar graph showing the selectivity of the products of the electrocatalytic reduction of CO2 using an integrated self-supporting gas diffusion electrode at different current densities in Example 5 of the present application.

[0031] Figure 4 It is a line graph comparing C2+ / C1 in the electrocatalytic CO2 reduction products of Example 5 of the present application and Comparative Example 1 at the same current density.

[0032] Figure 5 It is a line graph comparing the voltages corresponding to Example 5 of the present application and Comparative Example 2 at the same current density. DETAILED DESCRIPTION

[0033] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0034] In the description of the present application, it should be understood that the terms "upper", "lower", "horizontal", "inside", "outside", etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0035] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0036] In order to make the objectives, technical solutions and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0037] See also Figure 1 The method for preparing an integrated self-supporting gas diffusion electrode provided in an embodiment of the present application specifically includes the following steps S110 to S130, and its implementation method is described in detail below.

[0038] Step S110: Mix the conductive material, the catalyst and the pore-forming agent to form a mixed powder.

[0039] In this embodiment, the mass ratio of the catalyst to the conductive material is 1:50-50:1; the mass of the pore-forming agent is 0-50% of the total mass of the mixed powder. When the selected conductive material is carbon nanotubes, which have a pore structure, there is no need to use a pore-forming agent; the mass ratio of the hydrophobic polymer to the conductive material is 1:1-50:1 to ensure the mechanical strength of the electrode.

[0040] In this embodiment, the conductive material is in powder form, and the conductive material includes but is not limited to at least one of graphite, graphene, carbon nanotubes, acetylene black, Ketjen black, conductive carbon black, and activated carbon.

[0041] In this embodiment, the catalyst is in powder form, and the catalyst includes but is not limited to at least one of silver powder, copper powder, bismuth powder, nickel powder, cobalt powder, copper oxide, cuprous oxide, bismuth oxide, copper-silver alloy, copper-tin alloy, copper-zinc alloy, copper-nickel alloy, and nitrogen-doped carbon powder.

[0042] In this embodiment, the pore-forming agent is in powder form, and the pore-forming agent includes but is not limited to at least one of polyethylene glycol, polyvinyl alcohol, polyvinyl chloride, polymethyl methacrylate, and polylactic acid.

[0043] In this embodiment, the organic solvent includes but is not limited to at least one of ethanol, isopropanol, methanol, ethyl acetate, acetonitrile, N-methylpyrrolidone, and dimethylformamide.

[0044] In this embodiment, the hydrophobic high molecular polymer includes but is not limited to at least one of polytetrafluoroethylene, expanded polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polystyrene, and polypropylene.

[0045] Step S120: ball-milling the mixed powder, organic solvent and hydrophobic high polymer to obtain an electrode blank.

[0046] In this embodiment, the ball milling speed is 100-2000 rpm, and the ball milling time is 10-720 min, so as to ensure that each component is evenly distributed in the electrode blank.

[0047] In this embodiment, after the step of mixing and ball-milling the mixed powder, organic solvent and hydrophobic high molecular polymer to obtain an electrode blank, the following step is also included: rolling and shaping the electrode blank to obtain a sheet electrode, the rolling interval is 0.01-5mm, and the thickness of the sheet electrode is 50-500μm.

[0048] Step S130: heat-treating the electrode blank to obtain the integrated self-supporting gas-phase diffusion electrode.

[0049] In this embodiment, the step of heat treating the electrode blank to obtain the integrated self-supporting gas diffusion electrode specifically includes the following steps: heating the electrode blank to 100-400°C at a heating rate of 1-20°C / min and keeping it warm for 0.5-5h.

[0050] It should be noted that during the above heat treatment process, the pore former will undergo a decomposition reaction or be converted into a gaseous substance and then detach from the material. The hydrophobic polymer will soften when heated and then solidify when cooled to increase the mechanical strength of the electrode, thereby obtaining the integrated self-supporting gas diffusion electrode.

[0051] The integrated self-supporting gas diffusion electrode provided in the above-mentioned embodiment of the present application does not require the use of a binder, but instead confines the catalyst to the interior of the gas diffusion layer during the preparation process, thereby improving the utilization rate of the total active centers of the catalyst and effectively preventing the catalyst from falling off during the electrolysis process.

[0052] In addition, compared with the planar two-dimensional three-phase interface, the integrated self-supporting gas diffusion electrode provided in the present application has a three-dimensional structure. By constructing a stable hydrophobic microenvironment and an efficient electron transmission channel around the catalyst, the contact sites of the three-phase interface are significantly increased, thereby improving the selectivity of the electrocatalytic reaction under high current density and enhancing the operating stability of the entire electrolysis system.

[0053] The above technical solution of the present application is described in detail below in conjunction with specific embodiments.

[0054] Example 1

[0055] This embodiment provides an integrated self-supporting gas diffusion electrode, comprising the following steps:

[0056] (1) Weigh 1.2 g of multi-walled carbon nanotubes and 0.2 g of nano-Ag powder (20 nm), mix them to obtain a mixed powder, and transfer it to a ball mill;

[0057] (2) adding 7.5 mL of ethanol, 2.0 g of PTFE emulsion (60 wt%) and 6.0 g of zirconia balls, and milling at 1260 rpm for 30 min to obtain an electrode blank;

[0058] (3) adjusting the initial roller spacing to 5 mm to roll-press the electrode blank, and gradually reducing the roller spacing until a sheet electrode with a thickness of 180 μm is obtained;

[0059] (4) The sheet electrode was heat treated in a muffle furnace at a heating rate of 5°C / min, a heat treatment temperature of 380°C, and a holding time of 120 min to obtain an integrated self-supporting gas diffusion electrode, which was labeled as Ag-IGDE.

[0060] Table 1 shows the electrocatalytic performance of the electrode samples prepared in Example 1 at different current densities

[0061] <![CDATA[Current density / mA·cm -2 > 100 200 300 400 Faradaic efficiency of CO / % 92.78 91.04 89.33 85.01 <![CDATA[Faraday efficiency of H2 / %]]> 7.43 9.09 11.21 15.68

[0062] Example 2

[0063] The embodiment 2 provides an integrated self-supporting gas diffusion electrode, comprising the following steps:

[0064] (1) Weigh 1.2 g of multi-walled carbon nanotubes and 0.2 g of Cu2O, mix them uniformly to obtain a mixed powder, and transfer it to a ball mill;

[0065] (2) adding 7.5 mL of ethanol, 2.0 g of PTFE emulsion (60 wt%) and 6.0 g of zirconia balls, and milling at 1260 rpm for 30 min to obtain an electrode blank;

[0066] (3) adjusting the initial roller spacing to 5 mm to roll-press the electrode blank, and gradually reducing the roller spacing until a sheet electrode with a thickness of 180 μm is obtained;

[0067] (4) The sheet electrode was heat treated in a muffle furnace at a heating rate of 5°C / min, a heat treatment temperature of 380°C, and a holding time of 120 min to obtain an integrated self-supporting gas diffusion electrode, which was labeled Cu2O-IGDE.

[0068] Table 2 shows the electrocatalytic performance of the electrode samples prepared in Example 2 at different current densities

[0069] <![CDATA[Current density / mA·cm -2 > 100 200 300 400 Faradaic efficiency of C1 product / % 17.80 18.35 15.06 8.98 Faradaic efficiency of C2+ products / % 39.28 42.96 39.32 23.63 <![CDATA[Faraday efficiency of H2 / %]]> 43.34 39.19 46.43 68.15

[0070] Example 3

[0071] The embodiment 3 provides an integrated self-supporting gas diffusion electrode, comprising the following steps:

[0072] (1) Weigh 1.2 g of multi-walled carbon nanotubes and 0.2 g of nano Cu powder (<100 nm), mix them to obtain a mixed powder, and transfer it to a ball mill;

[0073] (2) adding 7.5 mL of ethanol, 2.0 g of PTFE emulsion (60 wt%) and 6.0 g of zirconia balls, and milling at 1260 rpm for 30 min to obtain an electrode blank;

[0074] (3) adjusting the initial roller spacing to 5 mm to roll-press the electrode blank, and gradually reducing the roller spacing until a sheet electrode with a thickness of 180 μm is obtained;

[0075] (4) The sheet electrode was heat treated in a muffle furnace at a heating rate of 5°C / min, a heat treatment temperature of 380°C, and a holding time of 120 min to obtain an integrated self-supporting gas diffusion electrode, which was labeled CuA-IGDE.

[0076] Table 3 shows the electrocatalytic performance of the electrode samples prepared in Example 3 at different current densities

[0077] <![CDATA[Current density / mA·cm -2 > 100 200 300 400 Faradaic efficiency of C1 product / % 12.44 10.34 8.15 6.33 Faradaic efficiency of C2+ products / % 45.65 37.06 34.85 27.55 <![CDATA[Faraday efficiency of H2 / %]]> 42.11 53.43 57.23 66.58

[0078] Example 4

[0079] The embodiment 4 provides an integrated self-supporting gas diffusion electrode, comprising the following steps:

[0080] (1) Weigh 1.2 g of multi-walled carbon nanotubes and 0.2 g of nano Cu powder (10-30 nm), mix them to obtain a mixed powder, and transfer it to a ball mill;

[0081] (2) adding 7.5 mL of ethanol, 2.0 g of PTFE emulsion (60 wt%) and 6.0 g of zirconia balls, and milling at 1260 rpm for 30 min to obtain an electrode blank;

[0082] (3) adjusting the initial roller spacing to 5 mm to roll-press the electrode blank, and gradually reducing the roller spacing until a sheet electrode with a thickness of 180 μm is obtained;

[0083] (4) The sheet electrode was heat treated in a muffle furnace at a heating rate of 5°C / min, a heat treatment temperature of 380°C, and a holding time of 120 min to obtain an integrated self-supporting gas diffusion electrode, which was labeled CuB-IGDE.

[0084] Table 4 shows the electrocatalytic performance of the electrode samples prepared in Example 4 at different current densities

[0085] <![CDATA[Current density / mA·cm -2 > 100 200 300 400 Faradaic efficiency of C1 product / % 33.95 21.89 15.87 13.04 Faradaic efficiency of C2+ products / % 47.10 52.14 44.99 33.75 <![CDATA[Faraday efficiency of H2 / %]]> 19.15 26.39 39.43 53.57

[0086] Example 5

[0087] The embodiment 5 provides an integrated self-supporting gas diffusion electrode, comprising the following steps:

[0088] (1) Weigh 1.2 g of multi-walled carbon nanotubes and 0.2 g of nano Cu powder (25 nm), mix them to obtain a mixed powder, and transfer it to a ball mill;

[0089] (2) adding 7.5 mL of ethanol, 2.0 g of PTFE emulsion (60 wt%) and 6.0 g of zirconia balls, and milling at 1260 rpm for 30 min to obtain an electrode blank;

[0090] (3) adjusting the initial roller spacing to 5 mm to roll-press the electrode blank, and gradually reducing the roller spacing until a sheet electrode with a thickness of 180 μm is obtained;

[0091] (4) The sheet electrode was heat treated in a muffle furnace at a heating rate of 5°C / min, a heat treatment temperature of 380°C, and a holding time of 120 min to obtain an integrated self-supporting integrated self-supporting gas diffusion electrode, marked as CuC-IGDE, see Figure 2 , is a SEM schematic diagram of the integrated self-supporting gas diffusion electrode prepared in Example 5.

[0092] Table 5 shows the electrocatalytic performance of the electrode samples prepared in Example 5 at different current densities

[0093] <![CDATA[Current density / mA·cm -2 > 100 200 300 400 500 Faradaic efficiency of C1 product / % 43.76 35.22 25.46 22.86 20.34 Faradaic efficiency of C2+ products / % 40.93 50.50 64.83 68.18 68.42 <![CDATA[Faraday efficiency of H2 / %]]> 15.69 14.57 10.43 9.06 11.53

[0094] Example 6

[0095] The embodiment 6 provides an integrated self-supporting gas diffusion electrode, comprising the following steps:

[0096] (1) Weigh 1.2 g of multi-walled carbon nanotubes and 0.1 g of nano Cu powder (25 nm), mix them to obtain a mixed powder, and transfer it to a ball mill;

[0097] (2) adding 7.5 mL of ethanol, 2.0 g of PTFE emulsion (60 wt%) and 6.0 g of zirconia balls, and milling at 1260 rpm for 30 min to obtain an electrode blank;

[0098] (3) adjusting the initial roller spacing to 5 mm to roll-press the electrode blank, and gradually reducing the roller spacing until a sheet electrode with a thickness of 180 μm is obtained;

[0099] (4) The sheet electrode was heat treated in a muffle furnace at a heating rate of 5°C / min, a heat treatment temperature of 380°C, and a holding time of 120 min to obtain an integrated self-supporting gas diffusion electrode, which was labeled Cu0.5C-IGDE.

[0100] Table 6 shows the electrocatalytic performance of the electrode samples prepared in Example 6 at different current densities

[0101] <![CDATA[Current density / mA·cm -2 > 100 200 300 400 Faradaic efficiency of C1 product / % 32.17 28.48 20.29 20.78 Faradaic efficiency of C2+ products / % 47.71 55.24 63.01 64.39 <![CDATA[Faraday efficiency of H2 / %]]> 20.61 16.58 17.27 15.21

[0102] Comparative Example 1

[0103] 1 mg of nano-Cu powder (25 nm) and 10 μL of Nafion solution were dispersed in 190 μL of isopropanol and dropped onto carbon paper to obtain a traditional layered integrated self-supporting vapor diffusion electrode based on carbon paper, which was labeled as CuC-CP.

[0104] Table 7 shows the electrocatalytic performance of the electrode samples prepared in Comparative Example 1 at different current densities

[0105]

[0106]

[0107] Comparative Example 2

[0108] (1) Weigh 1.2 g of multi-walled carbon nanotubes and transfer them to a ball mill;

[0109] (2) adding 7.5 mL of ethanol, 2.0 g of PTFE emulsion (60 wt%) and 6.0 g of zirconia balls, and ball milling at 1260 rpm for 30 min to obtain a carbon film blank;

[0110] (3) adjusting the initial roller spacing to 5 mm to roll-shape the carbon film blank, and gradually reducing the roller spacing until a sheet-like carbon film with a thickness of 180 μm is obtained;

[0111] (4) using a muffle furnace to heat treat the sheet electrode at a heating rate of 5°C / min, a heat treatment temperature of 380°C, and a holding time of 120min to obtain an integrated self-supporting carbon film;

[0112] (5) 1 mg of nano-Cu powder (25 nm) and 10 μL of Nafion solution were dispersed in 190 μL of isopropanol and dropped onto the self-made integrated self-supporting carbon film to obtain a traditional layered integrated self-supporting vapor diffusion electrode based on the carbon film, which was labeled as CuC-CF.

[0113] Table 8 shows the electrocatalytic performance of the electrode samples prepared in Comparative Example 2 at different current densities

[0114] <![CDATA[Current density / mA·cm -2 > 100 200 300 400 500 Faradaic efficiency of C1 product / % 43.33 40.44 37.50 32.21 23.62 Faradaic efficiency of C2+ products / % 40.43 46.07 49.03 53.07 56.75 <![CDATA[Faraday efficiency of H2 / %]]> 16.47 14.24 14.23 15.50 20.24

[0115] Effect verification

[0116] The performance of the integrated self-supporting gas diffusion electrodes of Examples 1-6 and Comparative Examples 1-2 of the present invention was evaluated using a gas diffusion electrolytic cell as an electrocatalytic reaction device. The specific measurement conditions were:

[0117] The gas products were detected by online gas chromatography (GC) with a sampling interval of 36 min.

[0118] The product was detected by Nuclear Magnetic Resonance Spectroscopy (NMR) with a test charge of 120C.

[0119] Gas phase diffusion electrolytic cell electrocatalytic performance test:

[0120] (1) Reference electrode: Hg / Hg2SO4 electrode;

[0121] (2) Counter electrode: high purity Pt sheet electrode;

[0122] (3) Working electrode: integrated self-supporting integrated self-supporting gas diffusion electrode (1×1cm 2 );

[0123] (4) Ion exchange membrane: Fumasep FAA-3-PK-130

[0124] (5) Electrolyte: 0.05M H2SO4+0.4M K2SO4 solution, 15mL;

[0125] (6) CO2 flow rate: 10 sccm

[0126] Faraday efficiency (FE) calculation:

[0127] The products of the electrochemical reaction include gas products and liquid products. For gas products, gas chromatography (GC) is used for quantitative analysis, and the Faraday efficiency calculation formula is:

[0128] In the formula, z is the number of transferred electrons; F is the Faraday constant (96485C·mo1 -1 );C i , the concentration of the target product (ppm×10 -6 ); v, the flow rate of the gas flowing out of the chromatogram (mL·s -1 ); j, reaction current density (A·cm -2 ); A, reaction area (cm2 ); R, gas molar volume (224000mL·mol -1 ).

[0129] For liquid products, nuclear magnetic resonance spectroscopy (NMR) was used for quantitative analysis, and the Faraday efficiency was calculated as follows:

[0130] In the formula, z is the number of transferred electrons; F is the Faraday constant (96485C·mo1 -1 );C i , the concentration of the target product (mol·L -1 ), V, volume of the solution where the product is located (L), j, reaction current density (A·cm -2 ); A, reaction area (cm 2 ), t, reaction time (s).

[0131] The electrode potential involved in the gas phase diffusion electrolysis cell is converted into the potential relative to the reversible hydrogen electrode by the formula E(vs.RHE)=E(Hg / Hg2SO4)+0.059*pH

[0132] In the formula, E(vs.RHE) is the electrode potential relative to the reversible hydrogen electrode (V); E(Hg / Hg2SO4) is the electrode potential of the Hg / Hg2SO4 electrode (0.652 V).

[0133] like Figure 3 As shown, it can be seen from Example 5 that when the integrated self-supporting gas-phase diffusion electrode provided by the present invention is used for the electrocatalytic CO2 reduction reaction, at a high current density at the ampere level, the Faraday efficiency of H2 is ~30%, and the hydrogen evolution reaction is significantly suppressed.

[0134] like Figure 4 As shown in Example 5 and Comparative Example 1, it can be seen that when the integrated self-supporting gas phase diffusion electrode provided by the present invention is used for the electrocatalytic CO2 reduction reaction, the C 2+ The product selectivity is greatly improved.

[0135] like Figure 5 As shown, it can be seen from Example 5 and Comparative Example 2 that the integrated self-supporting gas-phase diffusion electrode provided by the present invention has a lower voltage when used for the electrocatalytic CO2 reduction reaction.

[0136] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.

Claims

1. A method for preparing an integrated self-supporting gas diffusion electrode, characterized in that: The steps include: Mixing a conductive material, a catalyst and a pore-forming agent to form a mixed powder; Mixing the mixed powder, organic solvent and hydrophobic high molecular polymer and ball milling to obtain an electrode blank; The electrode blank is heat treated to obtain the integrated self-supporting gas phase diffusion electrode.

2. The method for preparing an integrated self-supporting gas diffusion electrode according to claim 1, characterized in that: The mass ratio of the catalyst to the conductive material is 1:50-50:1; the mass of the pore former is 0-50% of the total mass of the mixed powder; and the mass ratio of the hydrophobic high molecular polymer to the conductive material is 1:1-50:

1.

3. The method for preparing an integrated self-supporting gas diffusion electrode according to claim 1 or 2, characterized in that: The conductive material is in powder form, and includes but is not limited to at least one of graphite, graphene, carbon nanotubes, acetylene black, Ketjen black, conductive carbon black, and activated carbon.

4. The method for preparing an integrated self-supporting gas diffusion electrode according to claim 1 or 2, characterized in that: The catalyst is in powder form, and includes but is not limited to at least one of silver powder, copper powder, bismuth powder, nickel powder, cobalt powder, cupric oxide, cuprous oxide, bismuth oxide, copper-silver alloy, copper-tin alloy, copper-zinc alloy, copper-nickel alloy, and nitrogen-doped carbon powder.

5. The method for preparing an integrated self-supporting gas diffusion electrode according to claim 1 or 2, characterized in that: The pore-forming agent is in powder form, and includes but is not limited to at least one of polyethylene glycol, polyvinyl alcohol, polyvinyl chloride, polymethyl methacrylate, and polylactic acid.

6. The method for preparing an integrated self-supporting gas diffusion electrode according to claim 1 or 2, characterized in that: The organic solvent includes but is not limited to at least one of ethanol, isopropanol, methanol, ethyl acetate, acetonitrile, N-methylpyrrolidone and dimethylformamide.

7. The method for preparing an integrated self-supporting gas diffusion electrode according to claim 1 or 2, characterized in that: The hydrophobic high molecular polymer includes but is not limited to at least one of polytetrafluoroethylene, expanded polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polystyrene and polypropylene.

8. The method for preparing an integrated self-supporting gas diffusion electrode according to claim 1, characterized in that: In the step of mixing and ball-milling the mixed powder, organic solvent and hydrophobic high molecular polymer to obtain an electrode blank, the ball-milling speed is 100-2000 rpm and the ball-milling time is 10-720 min.

9. The method for preparing an integrated self-supporting gas diffusion electrode according to claim 1, characterized in that: After the step of mixing and ball-milling the mixed powder, organic solvent and hydrophobic high molecular polymer to obtain an electrode blank, the following step is also included: rolling and shaping the electrode blank to obtain a sheet electrode, the rolling interval is 0.01-5mm, and the thickness of the sheet electrode is 50-500μm.

10. The method for preparing an integrated self-supporting gas diffusion electrode according to claim 10, characterized in that: The step of heat treating the electrode blank to obtain the integrated self-supporting gas phase diffusion electrode specifically includes the following steps: The electrode blank is heated to 100-400° C. at a heating rate of 1-20° C. / min and kept at this temperature for 0.5-5 h.

11. An integrated self-supporting gas diffusion electrode, characterized in that: The integrated self-supporting gas diffusion electrode is prepared by the preparation method of any one of claims 1 to 10.

12. Use of the integrated self-supporting gas diffusion electrode as claimed in claim 11 in an electrocatalytic reaction.